2018
DOI: 10.1155/2018/1618051
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Inhibition of Helicobacter pylori Growth by Redox Cycling Phenylaminojuglones

Abstract: Infection by Helicobacter pylori increases 10 times the risk of developing gastric cancer. Juglone, a natural occurring 1,4-naphthoquinone, prevents H. pylori growth by interfering with some of its critical metabolic pathways. Here, we report the design, synthesis, and in vitro evaluation of a series of juglone derivatives, namely, 2/3-phenylaminojuglones, as potential H. pylori growth inhibitors. Results show that 5 out of 12 phenylaminojuglones (at 1.5 μg/mL) were 1.5–2.2-fold more active than juglone. Inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 55 publications
1
8
0
Order By: Relevance
“…The NADPHcytochrome P450 reductase enzyme catalyzes the reduction of an electron from Q7 to the semiquinone (•Q7) which becomes very reactive. This semiquinone •Q7 is reoxidized to the quinone in the presence of molecular oxygen, while oxygen is reduced to superoxide radical ( • O2 -) (Benites et al, 2018). We confirmed that Q7 causes oxidative stress in proteins.…”
Section: Q7 Induces Oxidative Stress and Role Of Ascorbatesupporting
confidence: 61%
“…The NADPHcytochrome P450 reductase enzyme catalyzes the reduction of an electron from Q7 to the semiquinone (•Q7) which becomes very reactive. This semiquinone •Q7 is reoxidized to the quinone in the presence of molecular oxygen, while oxygen is reduced to superoxide radical ( • O2 -) (Benites et al, 2018). We confirmed that Q7 causes oxidative stress in proteins.…”
Section: Q7 Induces Oxidative Stress and Role Of Ascorbatesupporting
confidence: 61%
“…Both AroQ and AroE (retrieved from metabolic pathway proteins and essential proteins analysis approaches) are involved in the chorismate synthesis, which is the precursor of folic acid and aromatic amino acids (phenylalanine, tyrosine, and tryptophan) that take part in protein and nucleic acid biosynthesis. Inhibition of folate biosynthesis is known to exert an anti-helicobacter activity [ 41 , 42 ]. DapB is involved in lysine biosynthesis via diaminopimelate, which are compounds used by bacteria to link peptidoglycan covalently to their cell wall.…”
Section: Discussionmentioning
confidence: 99%
“…Melting points (mp) were determined on a Stuart Scientific SMP3 (Staffordshire, UK) apparatus and are uncorrected. The record of IR, 1 H- and 13 C-NMR spectra, and chromatography procedures were done according to methods reported by Benites et al [ 27 ]. Proton nuclear magnetic resonance ( 1 H NMR) spectra were measured at 300 MHz in a Bruker Ultrashield-300 spectrometer.…”
Section: Methodsmentioning
confidence: 99%